Analyzing ’Malgudi Ki Kanhiya’ by R.K. Narayan: A Study of Malgudi’s Universe" - Anju (Innovative Research Thoughts, 2023)
In the novel "Malgudi Days," written by R.K. Narayan, the main character, Kanhiya, provides a fascinating look into the people who live in Malgudi and the town itself. An in-depth analysis of the literary piece "Malgudi Ki Kanhiya" written by the well-known Indian author R.K. Narayan is the primary topic of this presentation. The article digs into the complexities of this book, which takes place in the made-up town of Malgudi, which serves as the setting for many of Narayan's creative works. It examines how the narrative of Narayan not only functions as an engrossing tale but also functions as a microcosm of Indian society, representing the complexity, personalities, and cultural subtleties that are present in Indian culture. The purpose of this research is to shed light on how Narayan utilises the town of Malgudi as a canvas to show the many dimensions of human existence, social relationships, and the age-old moral conundrums that are confronted by the people who live there. This paper seeks to unravel the unique literary universe that R.K. Narayan crafted in "Malgudi Ki Kanhiya," offering insights into the richness and depth of his storytelling, through an in-depth analysis of the novel's characters, settings, and themes. This will be accomplished through a close reading of the novel.